The Effect Of Product Uniqueness And External Environmental Analysis On Competitive Advantage - Sinurat, Mangasi (Economic Development Progress, 2025)
Product uniqueness and external environmental analysis, towards competitive advantage in the context of strategic management. Product uniqueness is the basis for maintaining the company's competitiveness and relevance in a competitive market. External environmental analysis helps companies understand market dynamics and adjust their competitive strategies effectively. The research method applied uses information sources from e-books and e-journals that can be accessed for free, by applying qualitative descriptive analysis. The results of this study provide valuable insights for practitioners and researchers in developing comprehensive strategies to achieve and maintain competitive advantage in the dynamics of an ever-evolving business environment.